Characterisation of direct 3D sand printing process for the production of sand cast mould tools. Issue 1 (16th January 2017) - Hackney, Philip Mark; Wooldridge, Richard
Abstract : Purpose: Metal casting industry is in recovery phase after the crisis in 2008; customer demand continues to increase, with 98.6 million metric tons cast in 2011. Traditional ferrous and non-ferrous casting techniques require one shot or permanent moulds which require tooling to produce. Tooling particularly for developmental projects can be costly and take valuable time to produce. Additive manufacturing (AM) has been used to manufacture sand patterns for metal sand casting using laser sintering and sand bonding. This research aims to focus on characterising the sand-bonded process developed by ExOne GmbhH Germany. Design/methodology/approach: The approach taken in this research is to evaluate characteristics of parts built in the build volume for dimensional accuracy, tensile and compressive crush strength, density, impact strength and high temperature resistance. These properties are required to compare the 3D sand printing (3DSP) process to direct laser sand sintering (DLSS) and traditional Furan-based casting sand mixtures. The samples were taken from a production machine over a period of 30 days to ensure consistency. Findings: The 3DSP process has the capability to manufacture sand patterns to an accuracy of ±0.5 mm or error less than 0.3 per cent; it has also demonstrated the best build position to achieve accurate parts. The research has demonstrated the 3DSP patterns are comparable to traditional methods for important casting material characteristics such as tensile, compression and impact strength. It has been shown that the 3DSP process is capable manufacturing significantly larger parts, with build production rates up to 30 times higher compared to similar parts manufactured via the DLSS process. Research limitations/implications: As they has been very few 3DSP machines sold in Europe and particular UK, they has been little research into this new technique, and, therefore, they is a reliance on machine manufactures data for assessment. This research into 3DSP has increased the knowledge of this process significantly. Practical implications: This research would be of interest to designers and manufacturing engineers wishing to take advantage of the implications of having new design freedom, tool less manufacturing with short lead times in a wide range of materials using fundamentally tried and tested century's old casting techniques. Originality/value: The research for this paper revealed very little published academic research in this area; therefore, this work will increase the body of knowledge for this niche AM process.